Some Medicolegal Aspects of the Russian Cardiopulmonary Resuscitation Protocol - V. A. Kuksinsky; M.P. Tsiganova; K.V. Bykov; Yu. A. Churliaev (Общая реаниматология)
The purpose of the study was to analyze the Russian legislation to identify the medicolegal aspects of cardiopulmonary resuscitation, which are most significant for an intensive care anesthesiologist. Statutory acts concerning human health care, including those pertinent to cardiopulmonary resuscitation and those providing for the responsibility of medical workers in some cases were analyzed. A number of discrepancies in various legal acts concerning human death verification and resuscitative measures were identified. The analysis has revealed the aspects of cardiopulmonary resuscitation, which are, from the point of view of legislation, most important for the physician.